1984
DOI: 10.1007/bf00046625
|View full text |Cite
|
Sign up to set email alerts
|

Limnology of a desertic terminal lake, Walker Lake, Nevada, U.S.A.

Abstract: Walker Lake, a large terminal lake in west-central Nevada, is rapidly desiccating and becoming more saline. From 1937 to 1977, total dissolved solids increased from 5 650 to 10 650 mg 1 I. Ionically, the lake is a chlorocarbonate one; however, as desiccation continues it should eventually have about equal amounts of chloride, sulfate and carbonate. With regard to algal nutrients, the lake appears to be nitrogen limited. The phytoplankton is currently dominated by Nodularia spumigena; at times this produces nox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
(38 reference statements)
0
43
0
Order By: Relevance
“…Moreover, natural and man-made influences are causing some of these saline-alkaline lakes to dessicate, leading to further stress on resident populations (Galat et al, 1981;Cooper & Koch, 1984). These considerations stimulated us to quantify histological changes in organ tissues of Lahontan cutthroat trout living at various salinities and alkalinities.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, natural and man-made influences are causing some of these saline-alkaline lakes to dessicate, leading to further stress on resident populations (Galat et al, 1981;Cooper & Koch, 1984). These considerations stimulated us to quantify histological changes in organ tissues of Lahontan cutthroat trout living at various salinities and alkalinities.…”
Section: Introductionmentioning
confidence: 99%
“…In its present state, the Salton Sea is a highly eutrophic lake, characterized by high nutrient concentrations, high algal biomass, high fish productivity, low clarity, frequent very low dissolved oxygen (DO) concentrations, massive fish kills, and noxious odors (Holdren & Montaño, 2002). Nitrogen is a typical limiting nutrient of Great Basin terminal lakes including Pyramid Lake (Galat et al, 1981), Walker Lake (Cooper & Koch, 1984), Big Soda Lake (Cloern et al, 1983), Mono Lake (Herbst, 1998), and Great Salt Lake (Stephens & Gillespie, 1976). However, Holdren & Montaño (2002) reported orthophosphate to be frequently detected below the limit of 0.005 mg l -1 in the Sea, and concluded that algal growth is limited by phosphorus.…”
Section: Introductionmentioning
confidence: 99%
“…Mono Lake, California (Melack, 1983), Walker Lake, Nevada (Cooper & Koch, 1984) and Pyramid Lake, Nevada are examples. Continued diversion of water from these lakes is seriously threatening them as viable environments (Hammer, 1983).…”
Section: Introductionmentioning
confidence: 99%